Personnel Evaluation and Rating Errors in the U.S., China, and Germany - Zhu, Yunting (Transactions on Economics, Business and Management Research, 2023)
This paper examines performance management in Chinese, American, and German firms, highlighting the significance of knowledge-based employees in enhancing enterprise efficiency and success. It underscores the role of performance management in optimizing employee performance, aligning with strategic goals, and promoting organizational development. From both employee and enterprise standpoints, performance management offers various benefits, such as increased motivation, individual performance improvement, operational efficiency, strategic goal attainment, and workforce harmony. Nonetheless, common errors in employee performance assessment stem from cultural disparities, inappropriate appraisal methods, communication gaps, and inadequate training and supervision systems. This paper suggests pragmatic solutions to address these issues, including fostering the right evaluation mindset, clarifying assessment objectives, strengthening training and supervision mechanisms, promoting open communication, and cultivating a positive evaluation culture. These solutions are vital in enhancing the effectiveness and fairness of performance management in Chinese, American, and German companies, thereby contributing to their sustained growth and competitive advantage.